The long-run earnings effects of winning a mayoral election - Marco Bertoni; Giorgio Brunello; Lorenzo Cappellari; Maria De Paola (Università Cattolica del Sacro Cuore, Dipartimento di Economia e Finanza (DISCE), 2023)
We estimate the effect of winning a mayoral election on long-run licit earnings, which plays a key role in the selection of local political leaders. We use Italian administrative social security data from 1995 to 2017 and a sharp regression discontinuity design based on close elections. Over a 15-year horizon, the average present discounted value of winning an election is equal to 35,000 exteuro, or 85 percent of the annual labor and social security earnings for the average candidate in our sample, a modest effect driven by the compensations for political service and concentrated during the first five years after the election. Net of compensations for service, this effect is negative during the first ten years after the election, and almost fades away afterwards. Differences in the political careers of winners and runners-up and a two-term limit rule on mayors' office contribute to explain our results.
Keywords: D72; J44; J45; 330; returns to office; political selection; revolving door; rent-seeking; close elections